2007
DOI: 10.1038/sj.gene.6364380
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-dependent gene expression profile during maturation of dendritic cells

Abstract: Primary immune response to pathogens involves the maturation of antigen-presenting dendritic cells (DC). Bacterial lipopolysacharride (LPS) is a potent inducer of DC maturation, whereas the transforming growth factor b (TGFb) attenuates much of this process. Here, we analyzed the global gene expression pattern in LPS-treated bone marrow derived DC during inhibition of their maturation process by TGFb. Exposure of DC to LPS induces a pronounced cell response, manifested in altered expression of a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Others have shown that exposure of DCs to HES products downmodulates their expression of IL-12p40 (31). Similar observations have been made following exposure of DCs to TGF-b (52). In line with a role for TGF-bR signaling in HESmediated inhibition of DC migration, heat inactivation of HES, which destroys the TGF-b-like activity of HES, significantly diminished the inhibitory effect of HES on DC migration.…”
Section: Discussionsupporting
confidence: 70%
“…Others have shown that exposure of DCs to HES products downmodulates their expression of IL-12p40 (31). Similar observations have been made following exposure of DCs to TGF-b (52). In line with a role for TGF-bR signaling in HESmediated inhibition of DC migration, heat inactivation of HES, which destroys the TGF-b-like activity of HES, significantly diminished the inhibitory effect of HES on DC migration.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the spontaneous in situ maturation of TbR1-deficient LCs was associated with downregulation of E-cadherin and increased expression of CCR7, pointing toward an enhanced (e)migratory potential of the cells. Indeed, CCR7 gene activity in DCs can be inhibited by TGF-b signaling in vitro (39), and lower levels of E-cadherin as well as de novo expression of CCR7 are linked to LC dissociation from keratinocytes and migration toward local LNs (15,40).…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, Tgfb3 and Ifnra2 were up-regulated. The former is involved in inducing TGF-␤ and is considered an inhibitor of DC maturation (10), and the latter is involved in the production of alpha interferon and suppresses IL-12 production (7,32), evidencing for the first time that not only was the encapsulated strain unable to induce activation but that it was capable of activating the gene that regulated the production of alpha interferon and could be involved in the suppression of IL-12 production (7). Thus, the inability of DC to produce IL-12 following stimulation with encapsulated yeast could be related to the induction level of this gene and the activation of other signaling pathways that suppress IL-12.…”
Section: Discussionmentioning
confidence: 99%